Potret Kekerasan Terhadap Kaum Perempuan Yang Terjadi Di Dalam Novel “A Beautiful Mistake” Karya Saviana Jose - Eris Risnawati; Maharani Fitria (PIKTORIAL : Journal of Humanities, 2020)
The purpose of this study are (1) A portrait of women that occurs in the novel A Beautiful Mistake by Saviana Jose, and (2) violence against women that occurs in the novel A Beautiful Mistake by Saviana Jose. The research uses qualitative type with scientific method. The data in this research are sentences containing gender injustice in the novel A Beautiful Mistake. The data sources in this study are primary data and secondary data. Primary data sources used in this study are data taken from a collection of journals, books and other supporting articles such as magazines discussing gender injustice. The theory used in this study uses theory according to fakih, because the text is full of gender biases. The result in the novel A Beautiful Mistake there are several portraits and violence against women. Keywords: Portrait, violence, and gender.